Education and Training Drive Quality Growth of Generation Z: Pendidikan dan Pelatihan Mendorong Pertumbuhan Generasi Z yang Berkualitas - Nazwa, Naila; Rizky, M. Chaerul; Azzahra, Nabilah; Safitri, Dita; Fallah, M. Romzal (Indonesian Journal of Innovation Studies, 2025)
General Background: The rapid advancement of digital technologies presents both opportunities and challenges for rural youth, particularly those classified as Generation Z. Specific Background: In Desa Kurandak, Kecamatan Belawan, this cohort holds significant potential to contribute to local development, yet often lacks structured support. Knowledge Gap: Despite growing interest in youth empowerment, limited empirical evidence exists regarding the measurable impact of educational and training interventions on rural Gen Z populations. Aim: This study aims to analyze the role of education and training in enhancing the quality and capacity of Generation Z in Desa Kurandak. Results: Using a mixed-method approach with 44 respondents and linear regression analysis, findings reveal that education and training jointly have a significant effect (F = 100.657, p < 0.001) on youth development. Individually, education (t = 11.046, p < 0.001) and training (t = 3.060, p = 0.004) also show significant impacts. Diagnostic tests confirm no multicollinearity, normality of residuals, and homoscedasticity, with R² = 0.831. Novelty: This research uniquely integrates qualitative and quantitative evidence to validate the simultaneous and partial effects of educational variables on Gen Z development in a rural context. Implications: These findings advocate for integrated, collaborative programs involving governmental, educational, and private stakeholders to optimize Gen Z's role in village advancement. Highlights: Education and training significantly boost Gen Z potential in rural areas. Statistical analysis confirms strong predictive validity (R² = 0.831). Integrated efforts are essential for impactful youth empowerment programs. Keywords: Education, Training, Generation Z, Rural Development, Linear Regression